2002
DOI: 10.1103/physrevb.66.020407
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Jahn-Teller transition and resonant x-ray scattering in thin filmLaMnO3

Abstract: Epitaxial thin films of stoichiometric LaMnO 3 were grown on SrTiO 3 (110) substrates using the pulsed laser deposition technique. From the high resolution x-ray diffraction measurements, the lattice parameters were determined as a function of temperature and the cooperative JahnTeller transition was found to occur at T JT =573.0 K. Also measured was resonant x-ray scattering intensity of the orthorhombic (100) peak of LaMnO 3 near the Mn K edge from low temperatures to above T JT . We demonstrate that the int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…To further check the accuracy of the PACBED derived structure, in Table I we present experimentally measured and theoretically calculated crystal parameters of bulk LaMnO 3 at room temperature together with our results [5,8,35]. In terms of Mn-O bonding distances, the PACBED results are consistent with the neutron diffraction results within a few picometers, which may come from surface reconstruction and relaxation due to the finite size of the TEM specimen.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…To further check the accuracy of the PACBED derived structure, in Table I we present experimentally measured and theoretically calculated crystal parameters of bulk LaMnO 3 at room temperature together with our results [5,8,35]. In terms of Mn-O bonding distances, the PACBED results are consistent with the neutron diffraction results within a few picometers, which may come from surface reconstruction and relaxation due to the finite size of the TEM specimen.…”
supporting
confidence: 55%
“…The transmitted disk size is 9.7 mrad. [5,8,35]. It will be demonstrated that the JTD of octahedra in LaMnO 3 can be quantitatively measured by matching PACBED patterns in experimental and simulated PACBED patterns.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Experimentally, two early works from Raman spectroscopy [11] and from the analysis of the overall disorder in the EXAFS data across T * [12], supported the hypothesis of the upkeep of the local JT distortion. On the other hand the hypothesis that the local JT distortion may vanish and the Mn − O distances collapse, was sustained by the work in thin LaMnO 3 films [13]. The two distances found by the fitting procedure [13] collapse into a single one above a given temperature, in a similar way as the cell parameters.…”
Section: Introductionmentioning
confidence: 92%
“…This finding was supported by results obtained from different experimental techniques on La 0.95 Sr 0.05 MnO 3 single crystals, a series of Sr-doped powder samples and LaMnO 3 thin films. [16][17][18] Besides this general assessment concerning the character of the JT transition, the dynamical properties observed in a rather broad temperature range around T JT deserve a closer inspection. Recent Nuclear Magnetic Resonance (NMR) experiments 19 show changes in the spin-relaxation and the Knight-shift of the 17 O ligand ions already far below T JT , which are interpreted as a melting of the orbital order.…”
Section: Introductionmentioning
confidence: 99%